Finite element modeling of arc welded joints - Niw, Chang Chee; Abu Bakar, Abd. Rahim (Faculty of Mechanical Engineering, 2007)
In the past, researchers did not consider welded joints in their finite element models. This could give large discrepancies to the dynamic characteristics of the structure and consequently would lead to inaccuracies in their predicted results. This paper attempts to present an appropriate way to model welded joints in a structure using the finite element method. First, two single-plate were developed in 3-dimensional finite element model and then were validated using modal analysis. The two plates were joined together to form a single T-joint simple structure that considered arc-welded joints. Dynamic characteristics of the T-joint structure were determined by finite element analysis and experimental modal analysis and the predicted results were then compared with the measured data. Model updating was performed in order to increase accuracy of the predicted results. Finally, comparison of dynamic characteristics of the T-joint were made between rigid joints and arc-welded joints. Keywords: Modal analysis, finite element,